1996
DOI: 10.1006/dbio.1996.0347
|View full text |Cite
|
Sign up to set email alerts
|

Eph Family Receptors and Their Ligands Distribute in Opposing Gradients in the Developing Mouse Retina

Abstract: The Eph family of receptor tyrosine kinases and their ligands can be divided into two specificity subclasses: the Eck-related receptors and their GPI-anchored ligands, and the Elk-related receptors and their transmembrane ligands. Previous reports demonstrated that Eck- and Elk-related receptors in the retina distribute in high temporal-low nasal and high ventral-low dorsal gradients, respectively. While others have focused on complementary ligand gradients in the retinal axon target, the tectum, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 0 publications
2
95
0
Order By: Relevance
“…We investigated ephrinA5 protein expression in the retina and detected a high expression in the nasal part compared to the temporal one. This result is in accordance with the previously described retinal ephrinA5 expression pattern in the chick [51] and with ephrinA5 mRNA expression found in a high-nasal-to-low-temporal gradient in the developing mouse embryo retina [52]. As previously described, the mouse retinal ganglion cells also expressed EphA5 and EphA6 receptors [53].…”
Section: Discussionsupporting
confidence: 92%
“…We investigated ephrinA5 protein expression in the retina and detected a high expression in the nasal part compared to the temporal one. This result is in accordance with the previously described retinal ephrinA5 expression pattern in the chick [51] and with ephrinA5 mRNA expression found in a high-nasal-to-low-temporal gradient in the developing mouse embryo retina [52]. As previously described, the mouse retinal ganglion cells also expressed EphA5 and EphA6 receptors [53].…”
Section: Discussionsupporting
confidence: 92%
“…The pattern suggests that unknown retinal molecule(s) with peripheral to central gradients of distribution may be defective or modify photoreceptor degeneration in RP. Although intraretinal gradients of various molecules are present during development and postnatally (van Ginkel et al, 1995;Marcus et al, 1996;McCaffery et al, 1999;Schulte et al, 1999;Gru È n et al, 2000;Mic et al, 2000;Suzuki et al, 2000), to the authors' knowledge none of these gradients match the pattern of photoreceptor death found in concentric RP. Rather, the opposite is true for the distribution of one known photoreceptor survival factor, basic ®broblast growth factor, which is highest in rods in the far periphery and lowest in rods in the macula (Li, Chang and Milam, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…These data support a role for ALDHs in retinal compartmentalization and patterning and suggest that RA may serve as a position-specific tag involved in guiding retinal axons to their correct targets in the brain (12,16,17). Because ALDH1 is expressed at early stages of retinal development, prior to axon formation, asymmetry in RA levels may be required to mark the different axes of the retina and to form the basis for retinotectal organization, as previously suggested for some Eph receptors and their ephrin ligands (18,19).…”
Section: From the Department Of Oncology University Of Alberta And Cmentioning
confidence: 80%